Edukasi Pembelajaran Online Melalui Google Meet Pada Masa Pandemi dan Pembangunan Kawasan Pariwisata Desa Kaliagung - Panglipurjati, Puspaningtyas (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
In the odd semester of 2020, KKN is called KKN Society 5.0 where every KKN implementation process is done online and without the drop of participants to the location from the place of implementation. This is due to the COVID-19 pandemic that has hit the whole world where Indonesia has been affected by this pandemic. Kaliagung Village is one of the villages located in Kulon Progo regency which is one of the locations of kkn implementation. This village has the potential to be a tourist village because of beteng hill. In addition, since COVID-19, Kaliagung village must have a good education system. Because of these two things, a video was made planning the development of beteng hill area and a pocket book of knowledge how to use Google Meet as a learning medium for PAUD. Moreover. The data collection method used is literature studies, which are collected through websites, reports, maps, and videos. With the presence of this video and pocket book, it is hoped that it can support a better economy and education in Kaliagung village.